Low expression of human histocompatibility soluble leukocyte antigen-G (HLA-G5) in invasive cervical cancer with and without metastasis, associated with Papilloma Virus (HPV) - Guimarães, M. C. M.; Soares, Christiane Pienna [UNESP]; Donadi, Eduardo Antônio; Derchain, Sophie F. M.; Andrade, Liliana Aparecida Lucci de Angelo; Silva, Tarsia G. A. [UNESP]; Hassumi, M. K.; Simões, Renata T.; Miranda, Fabiana A.; Lira, Régia C. P.; Crispim, Janaína Oliveira; Soares, Edson Garcia (SAGE Publications, 2010)
Human leukocyte antigen-G (HLA-G) is a non-classical major histocompatibility complex class Ib molecule that acts as a specific immunosuppressor. Some studies have demonstrated that human papillomavirus (HPV) seems to be involved in lower or absent HLA-G expression, particularly in cervical cancer. In this study, we performed a cross-sectional study, systematically comparing the qualitative expression of the HLA-G5 isoform in invasive cervical carcinoma (ICC), stratifying patients according to the presence [ICC with metastasis (ICCW)] and absence [ICC without metastasis (ICCWT)] of metastasis, correlating these findings with interference of HPV and demographic and clinical variables. Seventy-nine patients with a diagnosis of ICC were stratified into two groups: ICCWT (n=52 patients) and ICCW (n=27). Two biopsies were collected from each patient (one from the tumor lesion and one from a lymph node). Immunohistochemistry analyses were performed for the HLA-G5 isoform, for HPV detection, and virus typing. HLA-G5 isoform molecules were detected in 25 cases (31.6%), 17 (32.7%) without metastasis and 8 (29.6%) with metastasis. HPV was detected in the cervical lesions of 74 patients (93.7%), but low expression of the HLA-G5 isoform was observed in all HPV-related cases. These findings are important; however, additional studies are necessary to identify the influence of HPV with HLA-G5 isoform expression on invasive cervical malignancies.
Keywords: Invasive cervical carcinoma; HLA-G5 isoform; HPV; Immunohistochemistry; PCR